Perlindungan Konsumen Terkait Praktik Pemasaran Yang Menyesatkan Melalui Media Digital Di Indonesia (Studi Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen) - Risky Tara Nabita Sari; Satino Satino (Jurnal Interpretasi Hukum, 2024)
Consumer protection serves as a legal effort to guarantee consumers’rights to clear, accurate, and non-misleading information. This study discusses misleading marketing practices in digital media and the legal protections provided to consumers in Indonesia under the Consumer Protection Act (UUPK) Number 8 of 1999. The objective of this study is to understand how existing regulations govern digital marketing and address the frequent issues that disadvantage consumers. The research method employed is normative juridical, using legal materials such as legislation, books, legal journals, and other scholarly articles. The findings indicate that while digital marketing significantly aids business actors in expanding their operations, consumers often find themselves in a vulnerable position as promotional information does not always align with reality and can be misleading. With the growing use of digital media as a marketing platform, there is an increasing need for strict regulations and effective complaint mechanisms to protect consumer rights. This study, alongside the enactment of the aforementioned law, aims to raise awareness among business actors regarding their responsibility to provide honest and transparent information, ultimately fostering a healthy business environment